2016
DOI: 10.1080/17460441.2016.1195945
|View full text |Cite
|
Sign up to set email alerts
|

Drug target identification in protozoan parasites

Abstract: Introduction Despite the fact that diseases caused by protozoan parasites represent serious challenges for public health, animal production and welfare, only a limited panel of drugs has been marketed for clinical applications. Areas covered Herein, the authors investigate two strategies, namely whole organism screening and target-based drug design. The present pharmacopoeia has resulted from whole organism screening, and the mode of action and targets of selected drugs are discussed. However, the more recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 137 publications
0
39
0
2
Order By: Relevance
“…HFF were cultured in Dulbecco's modified Eagle (DMEM) with phenol red, supplemented with 10% fetal calf serum (FCS) and 50U of penicillin/ml and were maintained as previously described [32]. For measuring cytotoxicity, HFF monolayers were grown in 96 well plates and were exposed to medium containing serial dilutions of BKIs (0.0009-20 μM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HFF were cultured in Dulbecco's modified Eagle (DMEM) with phenol red, supplemented with 10% fetal calf serum (FCS) and 50U of penicillin/ml and were maintained as previously described [32]. For measuring cytotoxicity, HFF monolayers were grown in 96 well plates and were exposed to medium containing serial dilutions of BKIs (0.0009-20 μM).…”
Section: Methodsmentioning
confidence: 99%
“…After culture at 37°C/5%CO 2 for 3 days, medium was discarded and cells were washed once with PBS. Cytotoxicity was measured by Alamar blue assay as described [32]. HepG2 (hepatocyte) or CRL-8155 (lymphocyte) cells were cultured as previously described [33] with minor changes.…”
Section: Methodsmentioning
confidence: 99%
“…Esta área, desarrollada mediante las herramientas biomoleculares (biología molecular, bioquímica, genética, etc. ), ha aumentado el número de blancos moleculares para pruebas en screening de alto rendimiento para identificación de agentes innovadores en las últimas décadas (7). Los blancos moleculares se definen como aquellas proteínas o ácidos nucleicos cuya actividad biológica es específica de un organismo y que pueden ser susceptibles a la acción de compuestos o moléculas con la capacidad de alterar sustancialmente su actividad.…”
Section: Nuevos Enfoques Terapéuticos Y Blancos Moleculares En Tripanunclassified
“…The design and chemical synthesis of antifungal molecules have been used as a method to evaluate the inhibition of mycelial growth or to inhibit the activity of specific proteins, as evaluated in F. graminearum [12][13][14]. In recent years, the search for new molecules has been based on the analysis of specific targets such as proteins, of which intracellular signaling proteins, cytoskeleton, membrane, or enzymes that participate in the metabolism have been proposed for the treatment of pathogenic species [15].…”
Section: Introductionmentioning
confidence: 99%
“…The main function of the TPI enzyme is to catalyze the interconversion of dihydroxyacetone phosphate into (D)-glyceraldehyde-3-phosphate; this process allows the two three-carbon molecules to continue being processed in the glycolytic pathway, since, without this reaction, there would be no net ATP production generated by the pathway [19]. Due to the relevance of this enzyme, some researchers have proposed the TPI as a potential target for the search (or synthesis) for new drugs [15][16][17][18], and even propose it as targets for the development of vaccines, of parasites that affect humans [16,20,21]. According to the aforementioned, it was in our interest to study the TPI of the fungus identified as F. oxysporum, since, despite being a pathogenic fungus of plants and/or humans, the analysis of biochemical characterization of this or another enzyme of the glycolysis had not been performed previously.…”
Section: Introductionmentioning
confidence: 99%